A mobilidade da pobreza no Brasil entre 1995-2019: uma análise a partir de dados de cortes transversais repetidos - Silva, Wellington Felipe dos Santos (2023)
Poverty mobility is a theme that has been growing within economic and political debates because it reveals the dynamic analysis of the situation of the poor that strongly helps the formulation of public policies. However, the main difficulty surrounding the investigation is the unavailability or scarcity of panel data needed to analyze their movements. This limitation makes it impossible to measure entry, exit, and stagnation movements, especially in developing countries where longitudinal surveys are rare. Some authors have suggested the use of synthetic panels built with cross-sectional data from current household surveys to solve the problem. Considering the existence of the National Household Sample Survey (PNAD), it becomes possible to apply this technique to measure the dynamics of poverty in Brazil. In addition, there are few works on the subject in the country. As a result, we use this proposal from an alternative statistical methodology of parametric determination to calculate the possible limits of probability that should contain the true movements in and out of poverty between 1995 and 2019. The findings revealed that Brazilian poverty was essentially chronic during the period, influenced by the 2015 national recession crisis and affecting individuals differently depending on gender and regional location. In this respect, women are more impacted by transient poverty, and the North and Northeast regions show the worst performances overall. Based on the conclusions, we can create a first profile of the dynamics of Brazilian poverty, making room for future research and improvement of current income assistance policies. Based on the conclusions, we can create a first profile of the dynamics of Brazilian poverty, opening a margin for future research and improvement of current income assistance policies.